As (in)capacidades estatais financeiras do Ministério do Turismo e seus efeitos na implementação das políticas de turismo - Rubens da Trindade (2023)
The thesis analyzes the effects of the financial capacities of the Ministry of Tourism (MTur) on the effectiveness of the actions of the tourism programs performed by this institution, as defined in the Planos Plurianuais (PPAs) between 2004 and 2019. The questions that guided the research were: how does the volume and the way of allocating MTur's financial resources affect the effectiveness of the implementation of the actions of its programs? Why are any actions greater or lower effective in their execution? Combined with financial capacity, how can bureaucratic capacity explain different performances of MTur programs? To answer these questions, the research was carried out in two phases, the first used a quantitative methodology to explain the dependent variable (effectiveness in the execution of MTur programmatic action goals in the Union's PPA) from the financial characteristics of budgetary actions, being independent variables: 1) the average participation of the action in the total budgetary expenditures of the MTur during the term of the PPA; 2) the average of resources variation destined to actions throughout the PPA; 3) the average of contingency or additional contributions to the action during its budgetary execution; 4) the percentage of participation of the parliamentary amendments in the expenses authorized for the action, and 5) the percentage of expenses of the action executed directly by the federal government (MTur). The results obtained by regression models indicated that actions with a higher percentage of direct execution by the MTur were more effective, which had an increase in the allocation of budgetary resources throughout their execution or whose resources had lower participation in parliamentary amendments. To better understand the effectiveness of the PPA actions and complement the analyzes performed in the first phase, the second phase of the qualitative research selected eight programmatic actions that were typical and atypical in the results of the first phase. Through interviews with key informants, the effects of the MTur's bureaucratic capacities were explored on the results of selected actions.The results indicate that in the case of the two typical actions, “Complete 2,300 works of tourist infrastructure”, which had high effectiveness and favorable financial conditions, was indeed benefited by a greater volume of resources, but also by the work of technicians from Caixa Econômica Federal. As for the action “Promotion, marketing and support for commercialization in the european market”, the low volume of available resources combined with the personnel shortage at MTur and EMBRATUR contributed to the low performance of the action. Regarding the six atypical actions analyzed, the badly performance of the action “Support for tourism infrastructure projects”, despite favorable financing conditions, seems to be explained by problems in planning, with an overestimation of the target. As for the other five actions, in which it is observed unfavorable financial conditions and high effectiveness, the explanation given for the action “Carry out 16 promotional campaigns aimed at the domestic market is its direct and centralized implementation in the MTur, combined with its high priority of execution by cause of the 2014 FIFA World Cup. For the other four actions, the good performance is attributed to the role of the bureaucracy in improving the projects and the underestimation of the goals at the beginning of the creation of the MTur, in 2003. Other aspects related to the political and regulatory dimension, especially regarding the participation of diverse actors in the implementation process, show up to be important for the effectiveness of actions, which recommends further studies on the subject. The general conclusion of the thesis is that the MTur has presented financial and bureaucratic fragility since its creation and, for this reason, had a low effectiveness in its actions, which reflected in the general low performance of the policy and inability to reach most of the goals stipulated between 2004 and 2019. With low participation in the Union budgetary, it lost resources in the analyzed period and had lower autonomy in budgetary execution, due to parliamentary amendments and transfers of resources to other entities of the federation. As to bureaucracy, in addition to the low number of public servants in relation to existing demands, the lack of career incentives motivates constant changes in the actors implementing the policy. However, it is observed that MTur technicians play an important role in project management, which contributes to increasing the effectiveness of some actions. As it is a new entity and has low bureaucratic capacities, the planning was an important aspect in explaining goals achieved much higher or lower than proposed. It is understood that the research findings contribute to the field of study and to public management, especially in relation to national tourism policies, by pointing out that there are weaknesses in the current policy.